The Gateway to Computer Science Excellence
0 votes
Simplify the following boolean function F together with the don’t care condition d; then express the simplified function in the sum of minterms.

(a)$F(x,y,z)=\sum(0,1,2,4,5) $

     $d(x,y,z)= \sum(3,6,7)$

(b) $F(A,B,C,D) = \sum(0,6,8,13,14)$

 $d(A,B,C,D) = \sum(2,4,10)$

(C) $F(A,B,C,D) = \sum(1,3,5,7,9,15)$

$d(A,B,C,D)= \sum(4,6,12,13)$
in Digital Logic by Boss (10.8k points) | 38 views

Please log in or register to answer this question.

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,741 questions
57,251 answers
104,648 users